Packing-induced solid-state fluorescence and thermochromic behavior of peptidic luminophores. Issue 1 (23rd December 2016) - Pramanik, Apurba; Haldar, Debasish
Abstract : In spite of its coumarin chromophore, supramolecular packing has an effect on the solid state fluorescent propensities of the peptidic luminophores. Abstract : The effect of packing on the solid state fluorescent propensities of peptidic luminophores has been investigated. A series of peptides containing 6-nitro-coumarin-3-carboxylic acid and α-aminoisobutyric acid (Aib) has been synthesized to study the structure–property relationship and stimuli responsive emission properties of the luminophores. In spite of the presence of a coumarin chromophore, peptide2 exhibits no solid state fluorescence. The alkyl chains of Aib affect the solid state molecular packing modes and optoelectronic properties significantly. However, the fluorescence microscopy confirmed the change of blue fluorescence of peptide3 in crystal and in amorphous states. The X-ray crystallography sheds some light on the molecular orientation, packing and the diverse degree of π–π stacking orbital overlap of adjacent coumarin chromophores of the peptide3 . Irrespective of coumarin chromophore, the peptides exhibit different packing-induced solid state emission properties varying from one peptide to another, which highlights the effect of Aib side chains.